Chromatic management in the evaluation of melanocytic lesions - Murillo, Mac Arturo (2023)
One of the most widespread criteria in the assessment of images of pigmented melanocytic lesions is the ABCDE method, in which color (C) is one of the relevant issues. However, most of its assessment is subjective, rarely considering the multiple factors that may affect image capture, processing, or observation, as well as human limitations and perceptual differences. This particularity can affect the early detection, diagnosis, and treatment of this type of skin lesions. With the development of diagnostic tele-dermatology and increasingly sophisticated AI algorithms, there is a need for objective procedures that optimize image processing so, it supports health professionals and effectively impact the increasing rates of melanomas. The purpose of this study is to provide a chromatic assessment methodology based on the CIEL*a*b* system and, better practices in image chromatic management, simplifying the procedures to a group of healthcare professionals who are not necessarily familiar with using color as an objective diagnostic tool.